Moss diversity of the cloud forest of the Sierra Juárez, Oaxaca, Mexico - Hernández-Rodríguez, Enrique; Aguirre Hidalgo, Victor (Instituto de Ecología, A.C., 2020)
Background and Aims: The cloud forest of the Sierra Juárez, Oaxaca, presents the highest level of conservation and is the largest in terms of extension in Mexico. Mosses are a key component of cloud forest flora, playing important ecological functions. However, the composition and moss diversity in this region remains unknown. Hence, our goals were to determine the floristic composition and estimate the α and β diversity of mosses in the cloud forest of the Sierra Juárez. Methods: The floristic composition of mosses in the cloud forest located within the municipality of Santiago Comaltepec, Oaxaca, was evaluated through eight sampling sites. In this forest, the diversity α and β of this floristic group were also estimated. The analyses were performed for all the species, as well as for the guilds of the terrestrial and epiphytic species. Key results: In this study, we registered 102 species of mosses, grouped into 64 genera and 32 families. Of those species, 13 are new records for the state. The most diverse families were Leucobryaceae and Orthotrichaceae. The genera with the highest number of species were Syrrhopodon, Campylopus, Fissidens, Macromitrium and Pogonatum. This study reports a high α and β diversity of mosses with a similar pattern between the terrestrial and epiphytic species. Conclusions: The cloud forest of the Sierra Juárez, Oaxaca, is an ecosystem with a high moss diversity and a great possibility of increasing the records for the state. Based on the analyses of estimated diversity, the need becomes evident to continue fundamental studies at the microenvironmental level on one of its most characteristic components.